Bi-efficacious incorporation of Indium in TiO2/PbS based nanocomposites for photocatalytic and solar paint applications. (1st November 2021) - Malik, Ayesha; Muhyuddin, Mohsin; Ali, Gohar; Wadood, Abdul; Tauqir, Anjum; Basit, Muhammad Abdul
Highlights: A multi-optional strategy for developing efficient TiO2 /PbS NCs is reported. Bi-efficacious incorporation of Indium uplifts the proficiency of p -SILAR. Resultant TiO2 -Pb(In)S-In2 S3 NC exhibits doubled photocatalytic performance. Incorporation of In also uplifts the photovoltaic performance as solar paint. An appreciable Jsc value of 3 mA/cm 2 is obtained with ∼1.5% PCE. Abstract: Quantum-dot (QD) sensitized TiO2 nanocomposites are currently emerging as efficient photovoltaic and photocatalytic materials and thus extensively investigated to obtain superior light harvesting. TiO2 coupled with PbS QDs (TiO2 /PbS) offers excellent absorbance of solar irradiation, ensuing significant electron-hole generation that can be utilized for carrying out photovoltaic activity in solar cells or dye degradation process. However, TiO2 /PbS nanocomposite suffers from detrimental charge carrier recombination and photo-corrosion in an electrolyte/aqueous environment which lowers down its performance. In this study, we have revealed the bi-efficacious role of Indium (In) incorporation during the conventional synthesis (i.e. successive ionic layer adsorption and reaction; SILAR) of TiO2 /PbS nanocomposite. Resultantly, the modified processes enabled us to achieve In-doped and In2 S3 deposited PbS QDs, which respectively produced improved opto-electronic behavior and photostability of TiO2 /PbS nanocomposites. On the one hand, In-incorporated TiO2 /PbS NC exhibited 100% higher degradation of toxic Congo Red dye than reference TiO2 /PbS, while it showed ∼3 mA/cm 2 higher photocurrent density (Jsc) and around 1.49% power conversion efficiency (PCE) when utilized for the development of solar paint-based photoanode in QDs sensitized solar cell (QDSSC). Along with extensive material characterization of reference and In-incorporated TiO2 /PbS NCs, electrochemical characterization was carried out to affirm the efficacy of modification of conventional SILAR process and resultant TiO2 /PbS NCs.